The Role of Long Non-coding RNAs in the Pathogenesis of RA, SLE, and SS - Gao, Yunzhen; Li, Shasha; Zhang, Zhongjian; Yu, Xinhua; Zheng, Junfeng (Frontiers in Medicine, 2018)
Rheumatoid diseases are a group of systemic autoimmune diseases which affect multiple organs with largely unknown etiology. In the past decade, long non-coding RNAs (lncRNAs) have emerged as important regulators of biological processes and contribute deeply to immune cell development and immune responses. Substantial evidences has been accumulated showing that LncRNAs involved in the pathogenesis of the rheumatoid diseases, including rheumatoid arthritis (RA), systemic lupus erythematosus (SLE) and Sjögren’s syndrome (SS). In this review, we summarize literature combined with bioinformatics methods to analyze the unique and common lncRNAs patterns in rheumatoid diseases and try to reveal the important function of lncRNAs in RA, SLE and SS.